Does Student Satisfaction Mediate the Correlation between E-learning Service Quality, Academic Engagement and Academic Achievement? - Jumaroh Ratna Satuti; Sunaryanto Sunaryanto; Dudung Ma'ruf Nuris (Universitas Negeri Malang, 2020)
This research aimed at analyzing the influence of e-learning service quality and academic engagement on academic achievement through student satisfaction as an intervening variable. Only students who had ever used e-learning service could be the research sample and 222 students were sampled using purposive sampling. The data were collected by distributing questionnaire to the research samples. The data were analyzed using path analysis technique. The result indicated that e-learning service quality, academic engagement, and student satisfaction had an influence on accounting students’ academic achievement. From this research finding, it was suggested that university lecturers keep on developing teaching and learning strategies which can improve students’ academic engagement since it has been proven that academic engagement has a dominant influence on students’ academic achievement.